Call of the void [videorecording (DVD)] - Cox, James B.; Carver, Caitlin, 1992-; Ellis, Richard, 1994- (Gravitas Ventures, 2025)
After the death of her brother, Moray tries to escape to a cabin in the woods when her retreat is derailed by a college band and their suspicious professor. They encounter a mysterious hum that once heard, there is no return.